Stepping into emotions: investigating the effect of angry and fearful faces on forward stepping and quiet stance - Lebert, Angélique; Vilarroya, Oscar; Stins, John (Frontiers in Human Neuroscience, 2024)
Facial expressions conveying an emotion may affect social interactions, such as approach-or avoidance-related behaviors. A specific facial feature is the gaze direction. An emotional facial expression such as anger will elicit distinct behavioral tendencies, depending on whether the angry gaze is directed toward the onlooker, or in a different direction. We tested whether facial expressions of anger and fear, combined with direct or averted gaze, elicit approachor avoidance tendencies, using a go/no-go variant of the whole-body stepping task.Method: Healthy adults stood on a force plate, recording the center of pressure (COP).Participants were presented with angry or fearful faces; either with direct or averted gaze.Participants had to identify the emotion, and -depending on instructions-either make a single step forward, or remain in a quiet stance. From the COP of the forward steps, we derived parameters such as reaction time and step size. From the quiet standing trials we derived parameters of postural sway, indicative of postural 'freeze'. We used analysis of variance to analyse the outcomes.Results and Discussion: First, we found that steps were initiated faster with angry faces than with fearful faces, in line with existing literature. Second, we did not observe a significant effect of gaze direction. Forward steps with direct and averted gaze had similar COP characteristics. Finally, we had expected to find freeze (postural immobility) with fearful faces, but this was also not observed. We discuss various explanations for the finding, and implications for research into the motoric grounding of social interactions.